Meretas Kebekuan Ijtihad Menghadap Arah Qiblat - Dhiauddin Tanjung (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2017)
AbstrakQibla (قبلة, also transliterated as Qiblah, Kibla or Kiblah) is an Arabic word for the direction that should be faced when a Muslim prays during Salat. Most mosques contain a niche in a wall that indicates the qibla. The qibla has importance to more than just the Salat, and plays an important part in everyday ceremonies.Kata-Kata Kunci : Qibla, jihah, syathrah, ‘Ainul Ka’bah, Mekah